Analysis Of Working Capital On Financial Performance At The Cooperative Of SMP Negeri 1 Kikim Timur, Lahat Regency - Herni Sohalia; M. Pahlan; Kasinem Kasinem (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to determine the effect of working capital on the financial performance of the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency. This study aims to determine the relationship between working capital and financial performance at the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency. The liquidity ratio calculation yields a Current Ratio > 1 (greater than one). This indicates that the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency, has current assets greater than its current liabilities from 2020 to 2024. This indicates a good liquidity position, and the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency, is able to meet its short-term obligations. The profitability ratio calculation indicates that the gross margin or contribution of the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency, from 2020 to 2024 is quite good. (Profitability ratio with good criteria generally with a ratio value above 10% - 15% is considered good enough), with this ratio value indicating that the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency is able to generate good profits from each sale, indicating efficiency in managing production costs and appropriate selling prices. The results of the solvency ratio calculation explain that the debt ratio value owned by the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency is quite high, where the debt ratio value is <1, where in this case a low solvency ratio (below 1) indicates that the assets owned by the Cooperative are mostly funded by debt. This could be an indication that the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency has a higher financial risk and may have difficulty paying its debt obligations, especially if there is a decline in financial performance or worsening economic conditions. The activity ratio calculation results indicate that the asset turnover ratio of the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency, for 2021-2023 was >1. This indicates the low efficiency and capability of the SMP Negeri 1 Kikim Timur Cooperative, Lahat Regency, in generating sales from its assets.